Systematic Literature Review dengan Metode Prisma: Pembelajaran Berdiferensiasi pada Pendidikan Dasar - Siringo Ringo, Sariaman (Jurnal Didaktika Pendidikan Dasar, 2025)
Since the implementation of the Merdeka Curriculum, differentiated instruction has increasingly become the focus of educators in Indonesia. Differentiated instruction is considered highly relevant to the current condition of students. This research investigates the trends and main findings from studies on differentiated instruction in elementary and middle school. A systematic literature review followed the PRISMA protocol to achieve this goal, focusing on articles published from 2020 to May 2024. The initial search on Google Scholar yielded 2,460 relevant article titles. Several inclusion and exclusion criteria were applied during the screening process, resulting in the analysis and qualitative synthesis of only 12 articles. The findings of this review indicate that the number of comparative studies on differentiated instruction in Indonesia has increased since 2022. Research on differentiated learning is mainly carried out in Mathematics and Natural Sciences subjects. The main findings from the reviewed articles show that differentiated instruction has a more significant impact than traditional instruction in enhancing the learning outcomes of elementary and junior high school students in areas such as conceptual understanding, critical thinking, and problem-solving skills. However, one article found different results regarding students’ autonomy. Most reviewed articles did not elaborate on the content, process, and product aspects used in the differentiated instruction under investigation.